2013
DOI: 10.1002/chem.201203640
|View full text |Cite
|
Sign up to set email alerts
|

An Examination of the Palladium/Mor‐DalPhos Catalyst System in the Context of Selective Ammonia Monoarylation at Room Temperature

Abstract: An examination of the [{Pd(cinnamyl)Cl}(2)]/Mor-DalPhos (Mor-DalPhos = di(1-adamantyl)-2-morpholinophenylphosphine) catalyst system in Buchwald-Hartwig aminations employing ammonia was conducted to better understand the catalyst formation process and to guide the development of precatalysts for otherwise challenging room-temperature ammonia monoarylations. The combination of [{Pd(cinnamyl)Cl}(2)] and Mor-DalPhos afforded [(κ(2)-P,N-Mor-DalPhos)Pd(η(1)-cinnamyl)Cl] (2), which, in the presence of a base and chlo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
49
0

Year Published

2014
2014
2024
2024

Publication Types

Select...
5
3
1

Relationship

4
5

Authors

Journals

citations
Cited by 74 publications
(49 citation statements)
references
References 68 publications
0
49
0
Order By: Relevance
“…[32] Moreover we sought to exploit, for the first time within a multicomponent reaction sequence of this type, the unusual ability of Mor-DalPhos/Pd catalyst mixtures to promote the selective mono-a-arylation of acetone. [15,33] In a preliminary test reaction (Scheme 2), (Mor-DalPhos)Pd(h 1 -cinnamyl)Cl (A [20] )/Mor-DalPhos mixtures proved useful in catalyzing the chemoselective monoarylation of octylamine with 1-chloro-2-iodobenzene, affording N-(2-chlorophenyl)octyl-A C H T U N G T R E N N U N G amine (B) in 96% isolated yield (4 mol% A/2 mol% Mor-DalPhos, toluene, Cs 2 CO 3 , 908C, 6 h unoptimized; see the Supporting Information for full details).…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…[32] Moreover we sought to exploit, for the first time within a multicomponent reaction sequence of this type, the unusual ability of Mor-DalPhos/Pd catalyst mixtures to promote the selective mono-a-arylation of acetone. [15,33] In a preliminary test reaction (Scheme 2), (Mor-DalPhos)Pd(h 1 -cinnamyl)Cl (A [20] )/Mor-DalPhos mixtures proved useful in catalyzing the chemoselective monoarylation of octylamine with 1-chloro-2-iodobenzene, affording N-(2-chlorophenyl)octyl-A C H T U N G T R E N N U N G amine (B) in 96% isolated yield (4 mol% A/2 mol% Mor-DalPhos, toluene, Cs 2 CO 3 , 908C, 6 h unoptimized; see the Supporting Information for full details).…”
Section: Resultsmentioning
confidence: 99%
“…Toluene was deoxygenated by sparging with dinitrogen followed by passage through an mBraun double column solvent purification system packed with alumina and copper-Q5 reactant and storage over activated 4 molecular sieves. Mor-DalPhos [13] and (Mor-DalPhos)Pd(h 1 -cinnamyl)Cl (A) [20] were prepared according to literature procedures; all other reagents, solvents and materials were used as received from commercial sources. Column chromatography was carried out using neutral alumina (150 mesh; Brockmann-III; activated).…”
Section: Experimental Section General Considerationsmentioning
confidence: 99%
“…In the specific context of BHA chemistry, Mor-DalPhos has proven to be particularly useful in the selective monoarylation of small, nucleophilic reaction partners (e.g. ammonia 14,23 and hydrazine 16 ), as well as in BHA cross-couplings of challenging aryl mesylate electrophiles. 21 Coordination chemistry studies have confirmed the ability of Mor-DalPhos to bind in a κ 2 -P,N fashion to palladium(II) centers.…”
Section: Ligand Variantmentioning
confidence: 99%
“…13 The phenols could then be converted into anilines in two simple steps by either a direct installation of the tosylamide or by an amination followed by a tosyl protection (Scheme 7). 14 …”
Section: Palladium-catalyzed Aminationmentioning
confidence: 99%